Culture, Cognition, and Internalization. (21st September 2021) - Lizardo, Omar
Abstract : In this paper, I address the history and systematics of the concept of internalization in cultural theory, noting that while use of the concept declined after its heyday in mid‐20th‐century functionalism, it is as indispensable now as it was then. I build an account of internalization consistent with recent conceptual distinctions offered in the culture and cognition literature. Taking the (relatively easy) case of the internalization of belief first, I problematize a popular conception of how declarative forms of personal culture are internalized via linguistic communication but flag a potentially promising solution. In this alternative story, the same "dialectical" model linking personal and public culture accounts for the internalization of both declarative and nondeclarative culture, allowing us to tell the same general story for the internalization of "knowledge‐that" and "knowledge‐how." I then discuss conceptual personal culture as a third general type of personal culture ("knowledge‐what"), standing between the purely declarative and nondeclarative. I show how the model of internalization developed in the case of beliefs and skills also applies to it with minor modifications. I close by outlining some implications of the theory developed here for clarifying such problems as theorizing degrees of internalization and the relative fragmentation of culture in persons.